Comparison of COVID-19 RT-PCR-Positive Patients in Oro-Nasopharynx Samples with RT-PCR Results in Simultaneous Stool Samples, Prospective Study - Burak Sarıkaya (İstanbul Medical Journal, 2024)

(untitled)
Introduction: The definitive diagnosis of coronavirus disease-2019 (COVID-19) infection is made by polymerase chain reaction (PCR) tests on nasopharyngeal and oropharyngeal swab samples. However, the presence of viral RNA has also been identified in stool samples. In this study, we aimed to investigate the relationship between severe acute respiratory syndrome-coronavirus-2 positivity in stool and the outcomes of COVID-19 disease. Methods: Fifty-four patients who were hospitalized between April-June 2020 and had positive COVID-19 PCR tests in nasopharyngeal and oropharyngeal swab samples were included in the study. PCR was performed on the stool samples of all patients. In addition, laboratory findings, clinical data, and computed tomography (CT) results of these patients were recorded and analyzed. Results: Among the patients, 13 out of 28 (46.4%) with positive fecal PCR test results were female, whereas 11 out of 26 (46.4%) with negative fecal PCR test results were female. Furthermore, 19 out of 28 patients (67.9%) with positive fecal PCR test results recovered, whereas 23 out of 26 patients (88.5%) with negative fecal PCR test results recovered. Notably, patients with fecal PCR-positive results exhibited more severe dyspnea, higher blood pressure, abnormal CT findings, and elevated D-dimer levels. Moreover, compared with patients with negative PCR results, those with positive fecal PCR results had lower levels of procalcitonin, hemoglobin, hematocrit, and lymphocytes. Conclusion: Considering the relationship between stool PCR positivity and the prognosis of the disease and laboratory test results, routine stool PCR tests may be useful, especially in COVID-19 patients presenting with gastrointestinal symptoms.